Bits on Chips - Veendrick, Harry; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides readers with a broad overview of integrated circuits, also generally referred to as micro-electronics. The presentation is designed to be accessible to readers with limited, technical knowledge and coverage includes key aspects of integrated circuit design, implementation, fabrication and application. The author complements his discussion with a large number of diagrams and photographs, in order to reinforce the explanations. The book is divided into two parts, the first of which is specifically developed for people with almost no or little technical knowledge. It presents an overview of the electronic evolution and discusses the similarity between a chip floor plan and a city plan, using metaphors to help explain concepts. It includes a summary of the chip development cycle, some basic definitions and a variety of applications that use integrated circuits. The second part digs deeper into the details and is perfectly suited for professionals working in one of the semiconductor disciplines who want to broaden their semiconductor horizon.
Part 1: An introduction to microelectronics -- The Electronics (R)evolution -- What is a chip? -- Basic concepts and definitions -- The chip development cycle -- Part 2: A deeper dive -- Digital circuits and IP -- Memory circuits and IP -- Analog IP, Interfaces and Integration -- Wafers and Transistors -- Lithography -- Fabrication -- Chip performance and power -- Testing and Yield -- Failure Analysis -- Packaging -- And, what is next? -- References -- Index.
Keywords: Electronic circuits; Computer science; Electronics; Electronic Circuits and Systems; Computer Science; Electronics and Microelectronics, Instrumentation